The missing pieces of the PuO2 nanoparticle puzzle. Issue 35 (10th July 2020) - Gerber, Evgeny; Romanchuk, Anna Yu.; Pidchenko, Ivan; Amidani, Lucia; Rossberg, Andre; Hennig, Christoph; Vaughan, Gavin B. M.; Trigub, Alexander; Egorova, Tolganay; Bauters, Stephen; Plakhova, Tatiana; Hunault, Myrtille O. J. Y.; et al.
Abstract : We report a full characterization of PuO2 nanoparticles at the atomic level and probe their local and electronic structure by a variety of methods available at the synchrotron and theoretical approaches. Abstract : The nanoscience field often produces results more mystifying than any other discipline. It has been argued that changes in the plutonium dioxide (PuO2 ) particle size from bulk to nano can have a drastic effect on PuO2 properties. Here we report a full characterization of PuO2 nanoparticles (NPs) at the atomic level and probe their local and electronic structures by a variety of methods available at the synchrotron, including extended X-ray absorption fine structure (EXAFS) at the Pu L3 edge, X-ray absorption near edge structure (XANES) in high energy resolution fluorescence detection (HERFD) mode at the Pu L3 and M4 edges, high energy X-ray scattering (HEXS) and X-ray diffraction (XRD). The particles were synthesized from precursors with different oxidation states of plutonium (III, IV, and V) under various environmentally and waste storage relevant conditions (pH 8 and pH > 10). Our experimental results analyzed with state-of-the-art theoretical approaches demonstrate that well dispersed, crystalline NPs with a size of ∼2.5 nm in diameter are always formed in spite of diverse chemical conditions. Identical crystal structures and the presence of only the Pu(iv ) oxidation state in all NPs, reported here for the first time, indicate that the structure of PuO2 NPs is very similar to that of the bulk PuO2 . All methods give complementary information and show that investigated fundamental properties of PuO2 NPs, rather than being exotic, are very similar to those of the bulk PuO2 .